Risk Perceived And Learning Achievement Analysis Of Participants Achievement on Procurement Training - Nur Basuki (JSSH (Jurnal Sains Sosial dan Humaniora), 2019)
Competence of human resources is an important factor in the procurement of government goods/services. For this reason, the government regularly holds training in procurement of goods / services. But this effort has not yet achieved optimal results. This can be seen from the learning achievements of the trainees. In the DKI Jakarta Province, training conducted from 2005 to 2016 only produced graduates of 18% per year. Therefore research is conducted to determine the factors that might be related to the low learning achievement of participants in the procurement of goods/services training. Various studies have been conducted in several Ministries/Institutions/Regions and found various factors related to learning achievement. This research was conducted to examine the relationship between the risks felt by participants and their learning achievements. This study uses a quantitative method with an explanatory approach to explain the relationship between these two variables. The results of the study show that there is a negative relationship between perceived risk and participants' learning achievement. The higher the risk felt by participants, the lower their learning achievement.